Seasonal variations in blood parameters of the Amazonian manatee, Trichechus inunguis - Elton P. Colares; Ioni G. Colares; Adalto Bianchini; Euclydes A. Santos (Brazilian Archives of Biology and Technology, 2000)
Seasonal variations in body weight, food consumption and blood glucose, total lipids, urea, total proteins, albumin and globulins of captive Amazonian manatees, Trichechus inunguis, were determined. Body weight changed significantly along the year, increasing from autumn to spring and decreasing in summer. The mean daily food intake of paragrass remained almost unchanged along the year. Paragrass administered to the manatees showed important variations in crude protein and lipid content along the year. No significant differences in blood parameters were registered between males and females in all seasons. Further, there were no significant differences in blood total proteins, albumin and globulins along the year. On the other hand, significant differences in the mean blood glucose, lipids and urea were registered. An increase in the blood glucose in the spring and summer was observed. Blood urea and lipids levels were positively related to paragrass protein and lipids content. These two correlations suggested that these blood parameters are good indicators of the animal nutritional status in the Amazonian manatee. Variações sasonais no peso do corpo, consumo de alimento e glicose, lípides totais, uréia, proteínas totais, albumina e globulinas do sangue de Peixes bois cativos, Trichechus inunguis, foram determinadas. Houve diferença significativa no peso dos animais ao longo do ano, sendo este aumento entre o outono e a primavera e decresce no verão. O consumo de capim colônia não variou ao longo do ano. A composição de proteína bruta e lipídeos totais de capim colônia dado aos animais mostrou importante variação ao longo do ano. Não foi verificado nenhuma variação nas concentrações dos parâmetros sagüíneos estudados entre os sexos em todas as estações. Também não foi verificado diferenças significativas nas concentrações sangüíneas de proteínas totais, albumina e globulinas ao longo do ano. Por outro lado, diferenças significativas nas concentrações de glicose, lipídeos e uréia foram verificadas. Um aumento na concentração de glicose foi observado na primavera e verão. As concentrações sagüíneas de uréia e lípides totais estão correlacionadas, respectivamente, com as quantidades de proteína bruta e gordura no alimento. Estas duas correlaçõessugerem que estes parâmetros sangüíneos são bons indicadores da condição nutricional do peixe-boi.